Governing Disasters, Its Challenges to Integrated Network of Emergency Preparedness: A Systematic Literature Review - Joel Rey Ugsang Acob; Heru Santoso Wahito Nugroho (Aloha International Journal of Health Advancement (AIJHA), 2018)
Disaster governance faces multiple challenges given the large variety and amount of resources, skills and expertise that adequate disaster response commands. Disasters do not necessarily respect territorial boundaries, or may overwhelm the capacity of any nation. Therefore, a collective, joint or even global effort becomes essential to overcome the crises. The paper is aimed to identify the nature of disaster governance and its challenges to integrated networks during emergency situation. The researcher utilized systematic integrative literature review using content analysis technique. Due to diverse potential findings, the review utilized a certain degree of limitations as criteria for selection. A multi-staging strategy was developed to identify the significant and relevant review literatures. Key words such as disaster, risk, management, emergency, governance were used to retrieve significant literatures. ProQuest is the only database used in the literature retrieval. The reviewer also limited the selection process by using considerable criteria. The literature is published from January 2015 to January 2017 internationally. Literatures were excluded if they did not meet the inclusion criteria set by the reviewer. Based from the analyses, literatures revealed that disaster governance is highly dynamic, complex, multi-level, multi-actor and fragmented and patchy in nature. Particularly, disaster governance takes place a broad range of both public and private sectors at various levels. This involves various phases of management, thus challenges the disaster governance. Furthermore, the literature unveiled that some of the challenges encountered by the disaster governance include people, limited resources, out-of-date or inaccessible materials, technology and jurisdictional politics. Therefore, it is concluded that emergency preparedness is an essential component of the disaster governance and the health care delivery system. Standardized strategies concerning disaster preparedness that allow flexibility in consideration of factors which challenges the governance. This creates a more comprehensive planning approaches and in turn, a more prepared citizens. Keywords: disaster governance, emergency preparedness, integrated network